Overexpression of the Maize psbA Gene Enhances Drought Tolerance Through Regulating Antioxidant System, Photosynthetic Capability, and Stress Defense Gene Expression in Tobacco - Huo, Yongjin; Wang, Meiping; Wei, Yangyang; Xia, Zongliang (Frontiers in Plant Science, 2016)
The psbA (encoding D1 protein) plays an important role in protecting photosystem II (PSII) from oxidative damage in higher plants. In our previous study, the role of the psbA from maize (Zea mays. L) in response to SO2 stress was characterized. To date, information about the involvement of the psbA gene in drought response is scarce. Here we found that overexpression (OE) of ZmpsbA showed increased D1 protein abundance and enhanced drought stress tolerance in tobacco. The drought-tolerant phenotypes of the OE lines were accompanied by increases of key antioxidant enzymes SOD, CAT, and POD activities, but decreases of hydrogen peroxide, malondialdehyde and ion leakage. Further investigation showed that the OE plants had much less reductions than the wild-type in the net photosynthesis rate (Pn), stomatal conductance (Gs), and the maximal photochemical efficiency of PSII (Fv/Fm) during drought stress; indicating that overexpression of ZmpsbA may alleviate photosynthesis inhibition during drought. qRT-PCR analysis revealed that there was significantly increased expression of NtLEA5, NtERD10C, NtAREB, and NtCDPK2 in ZmpsbA-OE lines. Together, our results indicate that ZmpsbA improves drought tolerance in tobacco possibly by alleviating photosynthesis reduction, reducing ROS accumulation and membrane damage, and modulating stress defense gene expression. ZmpsbA could be exploited for engineering drought-tolerant plants in molecular breeding of crops.